Conceptual framework for the application of Lean Healthcare considering human factors (Human Factors in Design, 2023)
This research presents the development of the framework Human Factors and Lean for Healthcare (HF&L4H) with the objective of addressing human factors in the principles of Lean Healthcare with a focus on the performance of the health system and human well-being. The framework was built from the identification of a need involving these two themes for improving processes in the health area, being applied experimentally in a University Hospital in Curitiba/PR, seeking to address problems related to process waste and demands of human factors in the location of surgical materials and ergonomic risks due to the need to handle materials due to their weight and storage location. The application showed promising results, showing the ease of locating materials on shelves, ease of reading and identifying labels and reducing the risk of injury or illness due to transporting heavy materials in inappropriate places.
Keywords: Lean Healthcare; human factors; system improvement; human well-being improvement